75 Association of complete street policies at the us state and county level with pedestrian fatalities, 1999–2015. (19th September 2017) - Quistberg, D Alex; Dang, Kolena; Magee, Caroline; Leonard, Julie; Yang, Jingzhen; Mooney, Stephen J; Rivara, Frederick P
Abstract : Statement of purpose: Complete Street policies have the potential to promote active transportation and reduce road injuries. This study examined the association between US county and state Complete Street policies and pedestrian fatalities. Methods: Complete Street policies were collated from Smart Growth America and geocoded to states (including Washington, DC) and counties. Pedestrian fatalities were obtained from the Fatality Analysis Reporting System for 1999–2014 and aggregated counts were calculated for each county by year. A difference-in-differences approach evaluated the association between polices and pedestrian fatalities. Generalised linear mixed models with Poisson distribution estimated incident rate ratios (IRRs) and 95% confidence intervals (95% CI) with year-county-population as offset. A random effect for policy was included at both state and county levels. Results: There were 71 694 pedestrian fatalities 1999–2000. Counties with a state policy only had a lower rate of pedestrian fatalities than counties in states without any policies (IRR 0.88, 95% CI 0.78, 0.98). The pedestrian fatality rate decreased annually in counties with no state or county policies by 1.5% (95% CI 0.9% to 2.0%). In counties in states with polices, but without county policies, the pedestrian fatality rate increased 1.2% annually on average (95% CI 0.1%, 2.3%). Other policy combinations were not statistically significant. Conclusion: The increase in pedestrian fatalities in counties with state Complete Street policies may be due to an increase in walking, a trend that has been observed in specific cities, though a similar significant trend was not observed in locations with county or county and state policies. Significance to Injury and Violence Prevention Science: Complete Street policies may be associated with an increase in pedestrian fatalities, though this may be due to an increase in walking in these counties and an overall decrease in non-policy counties.